Controlled Electrodeposition of Zinc Oxide on Conductive Meshes and Foams Enabling Its Use as Secondary Anode. Issue 10 (20th July 2018) - Stumpp, Martina; Damtew, Dominik; Stock, Daniel; Hess, Kevin; Schröder, Daniel; Schlettwein, Derck
Abstract : Both compact and porous zinc oxide (ZnO) films were electrochemically deposited out of aqueous zinc nitrate solutions under pulsed galvanostatic control onto different three-dimensional (3D) substrates. Gold and carbon meshes as well as copper and nickel foams were used as substrates, all having complex geometries in micrometer dimensions with high surface area. Electrodepositions of ZnO were controlled by regulating the most relevant parameters: the applied current density, the total deposition time, and the length of current pulses and pauses to avoid gas evolution interfering with film growth at the electrodes. Optimization of these parameters for each of the substrates allowed deposition of homogeneous ZnO films of the desired total film thickness. Potential-time curves measured during deposition helped to monitor film growth. Scanning electron microscopy (SEM) micrographs showed that pinhole-free ZnO films were deposited uniformly in a 3D manner on all substrates. X-ray diffraction (XRD) measurements confirmed the formation of highly crystalline ZnO films. Such electrodeposited ZnO films on electronic conductive substrates with high surface area are promising for application in energy storage and conversion systems – especially for secondary batteries with zinc anodes which was shown by cyclic voltammetry (CV).